Corporate financing and governance in Japan : the road to the future - Hoshi, Takeo (MIT Press, 2001)
Examines the evolution of Japanese corporate finance and governance from the 19th century through the late 1990s, analyzing bank-centered financing, regulation, and the transition toward capital markets.